The Multifactorial Contribution of Publications in Plastic Surgery Journals in Microsurgery Education. Issue 2 (February 2020) - Boczar, Daniel; Sisti, Andrea; Restrepo, David J.; Oliver, Jeremie D.; Huayllani, Maria T.; Ball, Colleen T.; Spaulding, Aaron C.; Cochuyt, Jordan J.; Rinker, Brian D.; Forte, Antonio J.
Abstract : Background: Microsurgery is one of the most complex operative skills. Recent restrictions on residents' working hours challenge residency program directors to ensure skill acquisition with scant time dedicated to microsurgery practice. We aimed to summarize the contribution of plastic surgery journals in microsurgical education. Methods: A comprehensive literature search was performed. Results: We observed an increasing number of publications on microsurgery education over the years. This could be due to the adoption of new technologies developed in the last 2 decades, the concerns about quality of resident training in the context of reduced work hours, the well-described benefit of medical simulations in other specialties, and the pressure on trainees to be proficient before operating on patients. The variety of aspects addressed in plastic surgery publications is broad: simulators, courses, skills assessment, national surveys, and technology trends. Conclusion: There is an upward trend in the number of publications and plastic surgery journals, demonstrating a remarkable contribution to microsurgery training.